SAT-295 An Extremely Rare Novel Missense Variant C.912G≫A; P.M304I in SOX3 Gene Is Responsible for X-Linked GH Deficiency in a Brazilian Boy Without Mental Retardation - Benedetti, Anna Flavia Figueredo (J Endocr Soc, 2020)
SOX3 (SRY-related HMG-box gene 3), located in the X chromosome, spans only one exon and is expressed in the infundibulum, diencephalon and hypothalamus. Alterations in SOX3, mainly deletions or insertions in the polyalanine tract, were associated with mental retardation, isolated GH deficiency (IGHD) or combined pituitary hormone deficiencies (CPHD). Missense variants are rare and only two were reported. Our aim was to find a molecular cause in patients with pituitary hormone deficiency and determine genotype-phenotype correlation. Twenty-eight patients (15F:13M) 24 CPHD:4 IGHD were selected for the study. Whole blood DNA was extracted using the Salting Out method. Library preparation was performed following Agilent’s SureSelectXT customized gene panel protocol containing 654 genes known to cause endocrine diseases. Illumina NextSeq 500 platform was used for sequencing at SELA. Alignment to genome reference hg19 was performed using BWA-MEM. Variants were called with FreeBayes and annotated by Annovar. Allele frequency ≤1% for exonic regions was considered in 1000 Genomes, gnomAD, ABraOM and SELA populational databases for variant filtering. Family segregation was done using Sanger sequencing. RNA and protein analysis were performed using mfold and YASARA, respectively. Protein models were made by I-Tasser. SOX3 missense variant (c.912G>A/p.M304I) was found in one male patient, without mental retardation, diagnosed with IGHD at the age of 7 years. After GH replacement, he reached final height at the age of 18 within family target height. Pituitary image showed an ectopic posterior pituitary, hypoplastic anterior pituitary and thin pituitary stalk. SOX3 (c.912G>A/p.M304I) variant in hemizygous state was absent in populational data banks. In silico prediction algorithms SIFT, PolyPhen, and Mutation Assessor were predicted as damaging. Family segregation showed normal mother and sister carriers of the variant, while father, brother and uncle (from mother’s side), all phenotypically normal, did not harbor the variant. RNA In silico analysis pointed that the variant causes mRNA structure change. Protein stability dropped from 677.46 kcal/mol in wild type to 666.69 kcal/mol in p.M304I, making it less stable. Protein Interaction analysis with DNA binding motif (PDB 2LE4) required two times less energy in mutant (376.19 kcal/mol) than wild type protein (646.77 kcal/mol), leading to a less stable interaction. We conclude that one among 28 patients presented a rare novel variant in SOX3 associated to IGHD in a patient without mental retardation and compatible with an X-linked inheritance pattern.